Modeling the Performance of a Towel Dryer in a Low-Temperature Microclimate System - Stepanova, N. D.; Snisarchuk, D. M. (Science and Transport Progress, 2025)
Purpose. The article is aimed at: investigating the operating conditions of a water-type towel dryer made of polished stainless steel AISI 304 in a low-temperature microclimate system; conducting a comparative analysis of the declared thermal power of towel dryers of the same design from different manufacturers, which will reveal significant differences between theoretical and real indicators; considering methods for determining the rated thermal power of a towel dryer, taking into account the forced movement of the coolant in the middle of the device pipeline, and so on. Methodology. The influence of various boundary conditions on compliance with the requirements of current regulatory documents for assessing the thermal efficiency of heating devices is analyzed. Numerical modeling of thermal processes in the SolidWorks Flow Simulation environment was used to study the operation of a towel dryer. The influence of the uncertainty of the blackness coefficient of the towel dryer surface on its thermal efficiency, as well as the role of the speed of air flow around the heat exchange surface, was evaluated. It was found that a decrease in the coolant temperature significantly affects the performance of the towel dryer: a decrease in the coolant temperature from 75 to 45 °C leads to a loss of 60–64 % of the heat output, and a decrease to 30 °C leads to a decrease in the output by 85.5–87.9 %. Findings. The results of modeling the thermal power of a towel dryer were compared with experimental data obtained in a certified laboratory. It was found that the results obtained by the first method correlate with laboratory tests to within 1 %, while the second method has an error of 5.6 %. The discrepancy between the results of modeling in SolidWorks Flow Simulation and laboratory tests is 20.23 %, which is due to the peculiarities of the computational models. Originality. The optimal design characteristics of heated towel rails for use in low-temperature systems have been determined, and recommendations for increasing the heat exchange surface of heated towel rails by optimizing the number and length of horizontal elements have been proposed. Practical value. Improving the reliability of calculations of the thermal capacity of towel dryers will help to improve their energy efficiency in modern heat supply systems. The results obtained can be useful for manufacturers of heating devices, heating engineers, as well as specialists involved in the design and modernization of heat supply systems for residential and public buildings.